2014
DOI: 10.5897/jene2014.0438
|View full text |Cite
|
Sign up to set email alerts
|

Recent limnological changes and their implication on fisheries in Lake Baringo, Kenya

Abstract: Water samples for physico-chemical analysis for this study were collected monthly for five years between April 2008 and March 2013. Conductivity, temperature, dissolved oxygen and pH was measured in situ using a Surveyor II model hydrolab. Chlorophyll-a concentration was determined using a Genesys 10S Vis spectrophotomer. Nutrients were determined using standard methods and procedures. Analysis of Variance (ANOVA) was used to determine spatial and temporal variation in physicochemical and biological factors. P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 14 publications
0
21
0
1
Order By: Relevance
“…It is characterised by relatively higher water pH (10) and almost three times higher salinity (conductivity, 10,590 μS/cm) than Lake Turkana, which has pH and a conductivity of 9.3 and 3420 μS/cm respectively (Avery 2010). Lake Baringo, a fresh water Lake located about 52 km from the Loboi swamp has DO concentration ranging from 5.89-6.7 mg/L, temperature range of 22.1-31.8°C, pH~8.5 and conductivity of about 580 μS/cm (Omondi et al 2014). Lake Victoria, also fresh water body is characterized by water temperatures ranging from 23.8 to 31.5°C, pH 6.2-9.2, and conductivity of approximately 170 μS/cm (Ochumba 1990;Crul 1995).…”
Section: Methodsmentioning
confidence: 99%
“…It is characterised by relatively higher water pH (10) and almost three times higher salinity (conductivity, 10,590 μS/cm) than Lake Turkana, which has pH and a conductivity of 9.3 and 3420 μS/cm respectively (Avery 2010). Lake Baringo, a fresh water Lake located about 52 km from the Loboi swamp has DO concentration ranging from 5.89-6.7 mg/L, temperature range of 22.1-31.8°C, pH~8.5 and conductivity of about 580 μS/cm (Omondi et al 2014). Lake Victoria, also fresh water body is characterized by water temperatures ranging from 23.8 to 31.5°C, pH 6.2-9.2, and conductivity of approximately 170 μS/cm (Ochumba 1990;Crul 1995).…”
Section: Methodsmentioning
confidence: 99%
“…2). The lake has surface and catchment areas of approximately km 2 and 6,820 km 2 , respectively, and a mean and maximum depth of 5.9 m and approximately 10 m, respectively, at high water levels (Omondi et al 2014). Lake Baringo waters remain fresh despite its shallow depth, a high net evaporation that characterizes the rift floor, and absence of a surface outlet.…”
Section: Lake Baringomentioning
confidence: 99%
“…The history of water quality measurements from Lake Baringo reveals that the geochemistry is greatly influenced by the rainfall patterns and the high evaporation rate (Omondi et al 2014). The decreasing trend of water transparency of Lake Baringo has been attributed to suspended solids brought into the lake from the catchment and resuspension of sediments by wind action (Wahlberg et al 2003).…”
Section: Geochemistrymentioning
confidence: 99%
See 1 more Smart Citation
“…Information on metal concentrations in bottom sediments of L. Baringo is lacking, yet catchment degradation, increasing lake water turbidity and changing lake water levels are environmental threats of concern in this area. Recently, temporal and spatial changes in the physical and temporal conditions showed that a general variation of physical and chemical parameters observed in the south-north transect was due to the effect of the affluent rivers and streams (Omondi et al, 2014). This study presents total concentrations of some of the priority metals, which were monitored in surficial sediments of two shallow freshwater lake basins to understand possible associated anthropogenic influences and processes.…”
Section: Introductionmentioning
confidence: 98%